2019
DOI: 10.1007/s12325-018-0861-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Metastatic Hormone-Sensitive Prostate Cancer Treatments: A Discrete Choice Experiment Among Men in Three European Countries

Abstract: IntroductionVarious treatment options are available for metastatic hormone-sensitive prostate cancer. This study aimed to quantify how men with prostate cancer in the United Kingdom (UK), Germany, and Spain perceive the risks and benefits of hypothetical abiraterone acetate plus prednisone treatment and docetaxel-based chemotherapy treatment options.MethodsA targeted literature review, exploratory interviews with prostate cancer patients and oncologists, and pre-test interviews were used to develop a discrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…For example, in castration-resistant prostate cancer or biochemically recurrent prostate cancer, fatigue was found to be an important risk attribute for patients, and one study observed that these patients valued reducing fatigue more than improving OS. 25,40 In another study, patients with advanced non-small cell lung cancer valued a reduction in fatigue severity from moderate to none equally as an additional 7.3 months of progression-free survival (with mild disease symptoms). 41 Taken together, these findings underscore the importance of carefully balancing the goal of improving survival with the introduction of treatment-related AEs.…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…For example, in castration-resistant prostate cancer or biochemically recurrent prostate cancer, fatigue was found to be an important risk attribute for patients, and one study observed that these patients valued reducing fatigue more than improving OS. 25,40 In another study, patients with advanced non-small cell lung cancer valued a reduction in fatigue severity from moderate to none equally as an additional 7.3 months of progression-free survival (with mild disease symptoms). 41 Taken together, these findings underscore the importance of carefully balancing the goal of improving survival with the introduction of treatment-related AEs.…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…28 Finally, a recent discrete choice experiment of prostate cancer patients and oncologists identified that treatment efficacy and pain control were similarly important when considering treatment choices. 29 In our study, treatment efficacy emerged as more important than pain control for mPCa survivors, with treatment efficacy identified as the fifth most strongly endorsed consideration. This underscores the importance of treatment efficacy and sequencing among mPCa patients.…”
mentioning
confidence: 67%
“…This implied these respondents did not perhaps understand the choice task” Damen, 2011 [ 69 ] “Passed the dominant question, demonstrating their understanding of the DCE task” To describe sample “A dominant choice set (i.e. a choice set in which both alternatives used implant material but one was characterised by logically preferable levels on all other attributes) and was included to test for rationality” “In total, 270 of 272 patients (99%) passed the dominant question, demonstrating their understanding of the DCE task” de Bekker-Grob, 2013 [ 81 ] “Experienced difficulty of the questionnaire” Not reported Not reported “93% of the respondents passed the rationality test that was included in the questionnaire, and 76% of the respondents did not find the DCE questions difficult” De Freitas, 2019 [ 52 ] “… comprehension and relevance of the attributes … as well as the survey instructions” To revise DCE instrument “Pretest interviews” “Participants … were able to answer all the questions, and … the instructions were clear and easy to understand. Some participants provided feedback about the wording of some of the attribute levels …” and “no changes to the number of choice tasks or to the experimental design were made on the basis of the pretest interviews” De Vries, 2015 [ 73 ] “Understand the task” To exclude participants “This dominant choice set was added to identify the responders who may not understand the task” NS—10 participants were excluded (assumed because they failed the dominant choice set) Fifer, 2018 [ 89 ] Online pilot with targeted feedback to ensure logic and understanding.…”
Section: Resultsmentioning
confidence: 99%
“…The 18 applied DCEs addressing understanding in the pretesting phase all used the concept of understanding as a way to modify or revise the DCE instrument before final roll out [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Most used pretesting to test or confirm understanding in relation to the terminology of attributes and medical concepts.…”
Section: Applied Dces Addressing Understanding In the Pretesting Phasementioning
confidence: 99%
See 1 more Smart Citation